PENGARUH GAYA HIDUP DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN WARKOP ONTAJAWA KABUPATEN GRESIK) - Maulana, Reza Rifanda Dwi Candra; Maulana, Maulana (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to evaluate the impact of lifestyle (x1) and reference group (x2) variables on purchase decisions (y), both individually and collectively. Utilizing a quantitative approach, the research involves 100 visitors to Warkop Ontajawa in Gresik, and analysis is performed using SEM-PLS with SmartPLS 3.0 software. The results indicate that both lifestyle (x1) and reference group (x2) variables have a significant impact on purchase decisions, with p-values < 0.05 for both variables. The F-test shows an F-value of 78.132, exceeding the F-table value of 3.090, indicating a significant simultaneous effect of both independent variables on the dependent variable, purchase decisions (y). In conclusion, both lifestyle and reference group significantly influence the purchase decisions of Warkop Ontajawa visitors